Economic risk exposure in stock market returns :|ba sector approach in South Africa (2007-2015) - Molele, Sehludi Brian (My University, 2019)
South Africa had targeted the oil and gas sector for investment through the industrial action plan as a special economic zone. However, certain economic fundamentals might negate the anticipated sector financial development. This study investigate how economic risk exposure influence oil & gas sector stock market returns from 2007 to 2015 on a monthly basis. The four macroeconomic variables used to measure economic risk exposure are Brent crude oil prices, the USD/ZAR exchange rate, broad money supply and gold prices. The adopted techniques include the GARCH model to incorporate volatility, the Johansen cointegration and Granger causality techniques. The results of the study found that change in Brent crude oil prices and broad money supply had a positive and significant impact on changes in oil & gas sector stock returns. Changes in exchange rate and gold prices had a negative and significant impact on the sector returns. The long-run relationship established one cointegrating equation in the series. Only Brent crude oil prices indicated a bi-directional Granger causality on the sector returns. Based on the findings, it is recommended that government may use exchange rate as a policy tool to attract interest in the sector. Regarding money supply, the reserve bank should further preserve its effective regulatory infrastructure including the laws, regulations and standards towards the achievement and maintenance of a stable financial system. Portfolio managers, risk managers and investors should monitor the gold price to mitigate losses due to its strength as a safe haven asset.
Thesis (M.A. Commerce (Economics)) -- University of Limpopo, 2019
Keywords: Stock returns; Oil prices; Exchange rates; Broad money supply; Gold prices; Stock-exchange -- South Africa; Petroleum overcharge restitution funds; Foreign exchange rates -- South Africa; Exchange rate pass-through